2019
DOI: 10.1155/2019/5416806
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Clinical Results of Vitrectomy and Scleral Buckling in Treatment of Rhegmatogenous Retinal Detachment

Abstract: Purpose. Most studies about retinal detachment cover a limited follow-up period. The purpose of this research is to assess the long-term results after pars plana vitrectomy (PPV) and scleral buckle (SB) surgery in patients with rhegmatogenous retinal detachment (RRD). Methods. 155 patients with RRD are treated either with SB or PPV with a mean follow-up of more than 5 years. Retrospective analysis of patient data with RRD was performed between January 2006 and June 2008 at a tertiary eye clinic. Results. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
0
11
0
3
Order By: Relevance
“…Die durchschnittliche Symptomdauer bis zur Vorstellung in der Klink war in der vorliegenden Untersuchung geringer als in der Literatur beschrieben [11,20,21]. Ein Vergleich mit Gesundheitssystemen, in denen der Hausarzt als Gatekeeper vor einem Facharztbesuch fungiert, ist jedoch nur bedingt aussagekräftig.…”
Section: Diskussionunclassified
See 2 more Smart Citations
“…Die durchschnittliche Symptomdauer bis zur Vorstellung in der Klink war in der vorliegenden Untersuchung geringer als in der Literatur beschrieben [11,20,21]. Ein Vergleich mit Gesundheitssystemen, in denen der Hausarzt als Gatekeeper vor einem Facharztbesuch fungiert, ist jedoch nur bedingt aussagekräftig.…”
Section: Diskussionunclassified
“…Eine Amotio retinae ist ein ophthalmologischer Notfall und führt unbehandelt zu einem progredienten Visusverlust [ 7 , 10 , 16 , 21 , 24 ]. Die häufigste Form ist dabei eine rhegmatogene Amotio retinae.…”
unclassified
See 1 more Smart Citation
“…2007; Schmidt et al. 2019). Strabismus and diplopia have been reported in up to 50% of patients 3–6 months after EX surgery (Smiddy et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [3] reported that a rRRD is rare at 2.3% at ≥6 months after PPV. However, there is very little information on late rRRDs, especially rRRDs that develop >10 years after the initial surgery, and most of these cases were treated by scleral buckling [4, 5].…”
Section: Introductionmentioning
confidence: 99%